Article review: the impact of fun and enjoyment on adult learning - Laily Yahya (Journal of English Language Teaching Innovations and Materials (Jeltim), 2019)
The article review of ‘The Impact of Fun and Enjoyment on Adult Learning’ (Lucardie, 2014) opens doors to the kaleidoscope of fun and enjoyment amongst adult learners. The essence of this review is an informative snapshot on the critical issues of how fun and joy have impacted adult learning through a qualitative research drawing upon traditions of phenomenology. It aims to explore the affective experiences of fun and enjoyment. This article review attempts to highlight an insightful assessment of the ideas and the arguments that are being discussed by the author. The different interpretation of this concept draws out contrasting elements between learners and teachers’ beliefs. A twist to this review is a reflective stance procured to address central issues emerging in the article related to the Malaysian context. It is through the lens of the reader, Continuous Quality Improvement (CQI):4R is proposed. This refers to the process of continuously improving the quality of teaching and learning of an educational programme. This review concludes with the framing of CQI:4R to illustrate reflect, revisit, realign and reconstruct processes that could possibly navigate the architectural landscape of the Malaysian Teacher Education.